Active colloids at fluid interfaces. Issue 17 (30th March 2016) - Malgaretti, P.; Popescu, M. N.; Dietrich, S.
Abstract : The motion of an active Janus particle trapped at a liquid-fluid interface is affected by a net torque due to the viscosity contrast between the adjacent fluid phases. The conditions under which translation along the interface occurs are analyzed. Abstract : If an active Janus particle is trapped at the interface between a liquid and a fluid, its self-propelled motion along the interface is affected by a net torque on the particle due to the viscosity contrast between the two adjacent fluid phases. For a simple model of an active, spherical Janus colloid we analyze the conditions under which translation occurs along the interface and we provide estimates of the corresponding persistence length. We show that under certain conditions the persistence length of such a particle is significantly larger than the corresponding one in the bulk liquid, which is in line with the trends observed in recent experimental studies.